Investigating of Macroecoprudential Assessment Against Economic Resilience During Pandemic Covid-19 - Haris, Helmi; Hasyim, Fuad; Hanafi, Syafiq Mahmadah (UIN Raden Mas Said Surakarta, 2023)
The Covid-19 pandemic has brought about changes in recent times, one of which impacts economic conditions. This study aims to investigate government policies through the National Economic Recovery (PEN) with a macroeconomic approach to the condition of economic resilience. Macroeconomic indicators use interest rates (IR), inflation, IHSG, money supply (MS), and tax revenues to see the effect on economic resilience, which consists of economic growth (GDP), unemployment, and poverty. The data used is a time series with an observation period from January 2017 to June 2021. The analytical method used is the Error Correction Model (ECM). The results show that the policy package through the National Economic Recovery (PEN) effectively overcame the economic downturn during the pandemic, although it is not yet fully optimal. At least policies based on fiscal and monetary can bring Indonesia's economic growth in a positive direction. So that in the long term, unemployment and poverty due to a decrease in people's purchasing power can be overcome.